Surgical treatment of abdominal wall weakness and lumbar hernias in Ehlers-Danlos syndrome – Case report. (2020) - Scheufler, Oliver; Andresen, Julian Ramin; Andresen, Reimer
Highlights: Ehlers-Danlos syndrome is a rare and diverse group of connective tissue disorders. Gastrointestinal manifestations are frequent in Ehlers-Danlos syndrome. Few publications have reported on surgical managment of Ehlers-Danlos syndrome. Multiple surgical interventions may be necessary if conservative treatment fails. Abstract: Introduction: Ehlers-Danlos syndrome (EDS) is a rare and diverse group of heritable connective tissue disorders. Gastrointestinal manifestations and abdominal pain are frequent in most subtypes of EDS. Conservative treatment is the standard of care. Presentation of the case: A 43-year-old female patient with genetically confirmed EDS classic subtype presented with diffuse gastrointestinal symptoms (bloating, belching and pain) that were controlled by the patient through inclined posture and external abdominal compression. A standard abdominoplasty with rectus muscle plication and mesh implantation lead immediately to complete relief of symptoms, which allowed the patient to assume an upright posture and resume all daily activities again. After 7 years, the patient was again seen with severe, persistent abdominal pain and inclined posture related to right lumbar herniations, as confirmed by MRI. However, there was no recurrence of the previous abdominal midline weakness and related gastrointestinal symptoms. Following lumbar hernia repair and mesh implantation, the patient was free of abdominal pain and resumed an upright posture again. Discussion: Although conservative treatment of EDS is primarily recommended and most surgeons are reluctant to operate on these patients except in life threatening situations, we present the successful surgical relief of disabling abdominal symptoms. Conclusion: Regarding the variability and complexity of symptoms in different subtypes of EDS, a personalized multimodal treatment including surgical approaches should be considered and achieved a significant and long-lasting improvement in quality of life in our patient.